ESTUDIO DE LA DISTRIBUCIÓN AUTOMATICA DE TELEFONIA DE LA EMPRESA CNT EN LA CIUDAD DE VINCES - CHONG BECILLA, JONATHAN DAVID (2019)
In Ecuador, the state must be to ensure that the infrastructure for connectivity and telecommunications cover the entire national territory, so that ICTs are available to the whole society in an equitable way. The provision of connectivity is a concurrent competition of the public sector and private sector, but it is the unavoidable responsibility of the State to address those sectors that have little attraction for private investment; guaranteeing, in this way, the progressive universal access of Ecuadorians, regardless of their geographical or economic position, of their condition age or gender, their physical condition or any other exclusionary factor. Fixed telephony is largely dominated by the public company, offering its service in a large part of the national territory, reducing the gap existing in access to Information Technology and the Communication in sectors with socioeconomic inequality. The fixed telephone sector in Ecuador is covered by 6 companies: CenturyLink, CNT fixed EP, CONECEL Fijo, EP EPTA, Linkotel S.A., Setel S.A. (El Comercio, 2018). In the province of Los Ríos, two companies offer fixed coverage, CNT with 44 682 subscribers and CONECEL Fixed with 4 subscribers, registered until October 2018. (ARCOTEL, 2018).